2004
DOI: 10.1016/j.jacc.2004.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Oxidative Stress in Hypercholesterolemia by Eccentric Isosorbide Mononitrate

Abstract: These data suggest that eccentric ISMN can completely inhibit the increase of vascular bioavailability of superoxide and partially prevent intimal lesion formation and endothelial dysfunction in hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…Vascular oxidative stress limits the bioavailability of endothelial NO and promotes atherosclerosis; while NO itself exerts antioxidative effects (21). It has been reported that NO donor isosorbide mononitrate could inhibit the increase in vascular bioavailability of superoxide and prevent IMT of the thoracic aorta in the cholesterol-fed rabbits (21). In the present study, we used the serum level of NOx as an indicator of NO.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vascular oxidative stress limits the bioavailability of endothelial NO and promotes atherosclerosis; while NO itself exerts antioxidative effects (21). It has been reported that NO donor isosorbide mononitrate could inhibit the increase in vascular bioavailability of superoxide and prevent IMT of the thoracic aorta in the cholesterol-fed rabbits (21). In the present study, we used the serum level of NOx as an indicator of NO.…”
Section: Discussionmentioning
confidence: 98%
“…Since NO has been reported to improve atherosclerosis (9), it is possible that NO produced by candesartan treatment may be related to the decrease in carotid IMT in the present study. Vascular oxidative stress limits the bioavailability of endothelial NO and promotes atherosclerosis; while NO itself exerts antioxidative effects (21). It has been reported that NO donor isosorbide mononitrate could inhibit the increase in vascular bioavailability of superoxide and prevent IMT of the thoracic aorta in the cholesterol-fed rabbits (21).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It has been shown that the relationship between endothelial dysfunction and relaxation response induced by acetylcholine is similar. 18 In a study about the effect of cholesterol, Sanz et al have indicated that the degenerative effect of hypercholesterolemia on endothelial responses was similar with cholesterol levels. 19 Even some studies have shown that resveratrol has an effect of decreasing serum total cholesterol levels; 20,21 on the other hand, some of the studies, similar to our results, found no significant changes in serum total cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a non-diseased cardiovascular system, O 2 ·-, NO, and other pro-oxidants and anti-oxidants are regulated. With onset of cardiovascular disease, the pro-oxidant/anti-oxidant balance is lost and pro-oxidants increase with an eventual decrease in anti-oxidant availability and antioxidant enzyme expression during chronic oxidative stress (Honing et al 1998;Hamilton et al 2004;Muller et al 2004), notably the RNS nitric oxide (NO). The oxidant imbalance is normally associated with increased O 2 ·-and decreased NO availability (Iuchi et al 2003;Zhang et al 2003).…”
Section: Oxidative Stressmentioning
confidence: 99%